2001
DOI: 10.1002/dc.2056
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic metaplastic carcinoma of the breast (MCB): An uncharacteristic pattern of presentation with clinicopathologic correlation

Abstract: Metaplastic carcinoma of the breast (MCB) is a well recognized but uncommon aberrant manifestation of poorly differentiated invasive carcinoma containing both epithelial (ductal) and mesenchymal elements as well as a transitional form between them. This heterogeneous tumor characteristically contains ductal carcinoma cells mixed with areas of diverse morphologic phenotype displaying spindle, squamous, chondroid, or osseous differentiation. Some studies have suggested that certain types of metaplastic carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…These metastases have an incidence ranging from 6 to 25% [12,13,17]. In non-metaplastic carcinomas, the frequency is higher (up to 47%) but still lower than in sarcomas [19]. …”
Section: Discussionmentioning
confidence: 99%
“…These metastases have an incidence ranging from 6 to 25% [12,13,17]. In non-metaplastic carcinomas, the frequency is higher (up to 47%) but still lower than in sarcomas [19]. …”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Unlike conventional invasive ductal carcinoma of the breast, metaplastic carcinoma tends to show hematogenous spread to the lung, pleura, bone, liver and brain in keeping with the sarcomatous phenotype, [10][11][12][13][14] with lymph node metastases seen infrequently. Thyroid metastasis has not been previously reported.…”
Section: Fine Needle Aspiration Cytology Of a Thyroid Metastasis Of Mmentioning
confidence: 99%
“…To date, the cytologic reports of metastatic metaplastic carcinomas are limited and consist mainly of single case reports. [7][8][9] It is not uncommon for only 1 component to be identified in the metastatic site, thereby leading to misinterpretation 4,11,15 ; that is especially true when clinical or radiologic information or review of previous pathology is not available. However, the clinical presentation and radiologic findings can also be misleading, as illustrated in the present case.…”
mentioning
confidence: 99%
“…Metastasis is rare, but when dissemination occurs, it is suggested that it bypasses the lymph nodes [1]. However, Khan et al [6] demonstrated in a case series that spindle cell carcinomas of the breast commonly metastasize to the axillary lymph nodes and that omitting node sampling may result in under-staging .…”
Section: Introductionmentioning
confidence: 99%
“…Many tumors are identified as metaplastic, indicating that the tumor deviates from the native tissue of the organ where it was found. For spindle cell metaplastic carcinoma, glandular epithelium transforms into nonglandular mesenchymal tissue [1].…”
Section: Introductionmentioning
confidence: 99%